Phylogeny of Strombidae (Gastropoda) Based on Mitochondrial Genomes - Li, Fengping; Zheng, Jiawen; Ma, Qingxia; Gu, Zhifeng; Wang, Aimin; Yang, Yi; Liu, Chunsheng (Frontiers in Marine Science, 2022)
The marine gastropod Strombidae is widely distributed in tropical and subtropical regions all over the world and possesses high morphological diversity. In order to better understand how morphological characteristics evolved within Strombidae, a robust phylogenetic framework is needed. In the present study, the complete mitochondrial genomes of Lentigo lentiginosus, Euprotomus aratrum, and Canarium labiatum were sequenced. The three newly sequenced mt genomes contained 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, two ribosomal RNA (rRNA) genes, and several non-coding regions, indicating a similar pattern with respect to genome size, gene order, and nucleotide composition compared with those of other strombids reported before. Two different datasets derived from mitochondrial genes were constructed to resolve the internal phylogenetic relationships of Stromboidea and Strombidae. Within Stromboidea, the sister group formed by Clade I [Rostellariidae + (Seraphsidae + Strombidae)] and Clade II [Xenophoridae + (Struthiolariidae + Aporrhaidae)] were fully recovered and supported by morphological synapomorphies as previously suggested. The phylogenetic positions of L. lentiginosus, E. aratrum, and C. labiatum were confirmed within Strombidae, and several morphological similarities were observed corresponding to the present phylogeny. A correlation between strombids speciation events and paleoclimate change was presumed. Our results indicate that complete mt genomes would be a promising tool to reconstruct a robust phylogeny of Strombidae with an increased taxon sampling in the future.